2021
DOI: 10.1002/jcaf.22483
|View full text |Cite
|
Sign up to set email alerts
|

Real earnings management in bankrupt firms

Abstract: We investigate: (1) whether managers in bankrupt firms manipulate earnings through real earnings management (REM); (2) the incentives and tradeoff strategies to engage in REM; (3) how REM influences the subsequent firm performance and bankruptcy probability. We find that bankrupt firms are more likely to manipulate earnings via REM than continuous firms. There is an increasing trend of REM activities in the 5‐year window before bankruptcy. The major incentive for bankrupt firms to engage in REM is the issuance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Investor protection is a crucial factor in determining how earnings are managed globally, according to research by Xu et al (2021). They investigate whether the prevalence of earnings management diminishes as investor rights and safeguards and legal enforceability rise through a survey of 8,000 enterprises from 31 countries utilising 9 years of data.…”
Section: The Legal Side Of Earnings Managementmentioning
confidence: 99%
“…Investor protection is a crucial factor in determining how earnings are managed globally, according to research by Xu et al (2021). They investigate whether the prevalence of earnings management diminishes as investor rights and safeguards and legal enforceability rise through a survey of 8,000 enterprises from 31 countries utilising 9 years of data.…”
Section: The Legal Side Of Earnings Managementmentioning
confidence: 99%
“…Their result shows that earnings management has no relationship with bankruptcy risk, while business strategy has positive and significant effect towards bankruptcy risk. Chunhao et al (2021) focused their research on three issues. Firstly, whether managers in bankrupt companies manipulate earnings through real earnings management (REM).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This fact has motivated managers to move accrual earnings management practices to real earnings management practices or also known as real activity manipulation. Significantly different from accrual earnings management practices, real activity manipulation utilizes and changes the firm's basic economic activities to deliver a real economic effect on firm performance (Xu et al, 2021), affecting cash flows by changing business operations (Wang & Zheng, 2020), and using the timing of transactions made throughout the year to achieve profit targets (Khunkaew & Qingxiang, 2019). A survey of 401 managers led by Graham et al (2005) found that 78% of managers are more inclined to commit real activity manipulation even though they are aware of the risk of negatively long-term consequences on company performance.…”
Section: Introductionmentioning
confidence: 99%
“…Real activity manipulation is a form of earnings management by changing and regulating earnings to be reported in the financial statements through suboptimal operating activities such as sales manipulation, excessive production, cutting research costs, and R&D development (Xu et al, 2021). Real activity manipulation can also be carried out by regulating changes in important economic policies that are prepared for the company's long-term operating activities such as a policy of delaying investment or reducing necessary expenses and expenditures (Ipino & Parbonetti, 2017; Gao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%